2020
DOI: 10.1002/ppul.25042
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for atopic diseases and recurrent respiratory tract infections in children

Abstract: Introduction: The simultaneously increased prevalence of atopic diseases and decreased prevalence of infectious diseases might point to a link between the two entities. Past work mainly focused on either atopic diseases or recurrent infections. We aim to investigate whether risk factors for atopic diseases (ie, asthma, allergic rhinitis, atopic dermatitis, and/or food allergy) differ from risk factors for recurrent respiratory tract infections (RRTIs) in children. Methods: Cross-sectional data were used from 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 30 publications
2
17
0
3
Order By: Relevance
“…Regarding children's age, the odds of URTI in children aged 7-12 and 13-17 years was lower than that in children aged 0-1 year, and no significant difference was observed in children aged 2-6 years. This is quite similar to the study reported by Kansen et al (7) The possible reason was that sinus development and immune system in children above 7 years were maturing to prevent virus infections.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding children's age, the odds of URTI in children aged 7-12 and 13-17 years was lower than that in children aged 0-1 year, and no significant difference was observed in children aged 2-6 years. This is quite similar to the study reported by Kansen et al (7) The possible reason was that sinus development and immune system in children above 7 years were maturing to prevent virus infections.…”
Section: Discussionsupporting
confidence: 91%
“…Although URTI is rarely fatal, it is a source of severe morbidities and causes some complications, thereby increasing medical costs and bringing a considerable economic burden ( 5 , 6 ). Many factors make children vulnerable to URTI, many of which are preventable ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was more pronounced in children who started daycare before the age of one than in children who started attending daycare after the age of two [79]. In contrast, a recent study of 5517 participants aged 1 to 18 years did not show an increased risk of atopic diseases (including food allergy) in children attending daycare during the first year of life [80]. Similarly, Koplin et al revealed lower risk of challenge-proven egg, sesame and peanut allergy in children at daycare in the first six months of life compared to those cared for at home [81].…”
Section: Daycarementioning
confidence: 64%
“…One study reported that lower respiratory tract infection in the first year of life is associated with allergic rhinitis in children [ 46 ]. Kansen et al showed that the concurrent presence of recurrent respiratory tract infections increased the odds of having asthma or allergic rhinitis, while it reduced the odds of having atopic dermatitis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%